The impacts of COVID-19 on China insurance industry—An empirical analysis based on event study - Wu, Xuan; Wang, Chan; Wen, Hong-xing; Nie, Pu-yan; Ye, Jin-fa (Frontiers in Public Health, 2022)
Since December 2019, the COVID-19 has been raging around the world. In order to identify the impacts of COVID-19 on China's insurance industry, this paper uses the event study method to caculate the changes in the cumulative abnormal return rate and the cumulative excess return of Chinese listed insurance companies before and after the outbreak of COVID-19. In the empirical analysis, five different typical events are examined, including the first outbreak of COVID-19 in China, the closure of Wuhan, the dredging of Wuhan, and the listing of vaccines in China. The results show that the return rate of listed companies in the insurance industry showed an "inverted N" curve with the “decreasing, rising and then decreasing”. The epidemic mainly has negative effects on the insurance industry in terms of premium income and indemnity expenditure. According to the supply shock theory of the new supply economics, the epidemic has a negative impact on the insurance industry in the short term and a positive impact in the long term. In this context, insurance enterprises should attach importance to the change of business model, strengthen the development model of public-private joint venture insurance, promote product innovation and the application of insurance technology, and the experience and practice of the insurance industry in responding to the impact of the epidemic are of great significance to the transformation of China's insurance industry.